Production of extracellular material by streptococci associated with subacute bacterial endocarditis. - Straus, D C (1977)
Six strains of viridans streptococci isolated from confirmed cases of subacute bacterial endocarditis were studied for production of extracellular material. All six strains, when grown to the exponential phase, produced exoproducts that had similar elution profiles on a G-100 Sephadex column. Since essential nutrients, such as amino acids, may be periodically growth limiting to streptococci in the fibrin-covered lesions on heart valves, the potential to elaborate extracellular protein and other material by streptococci that were deprived of essential amino acids was studied. Examination of supernatant fluids from cultures of Streptococcus MG intermedius deprived of glutamate and cystine revealed the presence of a complex mixture of extracellular materials in amounts comparable to those produced by normallly growing cells, Although only a slight (21 to 24%) increase in total protein occurred during amino acid deprivation of 12 h, the extracellular material contained numerous protein components, several of which demonstrated proteolytic activity. On a cell dry weight basis, the amino acid-deprived cells produced four-to eightfold more protease(s) than did exponential cells grown in complete medium. These results demonstrate that viridans streptococci are capable of elaborating potentially damaging compounds even when their multiplication has been arrested by nutritional deprivation.